Crocetin and Its Glycoside Crocin, Two Bioactive Constituents From Crocus sativus L. (Saffron), Differentially Inhibit Angiogenesis by Inhibiting Endothelial Cytoskeleton Organization and Cell Migration Through VEGFR2/SRC/FAK and VEGFR2/MEK/ERK Signaling Pathways - Zhao, Chen; Kam, Hio-Tong; Chen, Yan; Gong, Guiyi; Hoi, Maggie Pui-Man; Skalicka-Woźniak, Krystyna; Dias, Alberto Carlos Pires; Lee, Simon Ming-Yuen (Frontiers in Pharmacology, 2021)
Crocetin and crocin are two important carotenoids isolated from saffron (Crocus sativus L.), which have been used as natural biomedicines with beneficial effects for improving the suboptimal health status associated with abnormal angiogenesis. However, the anti-angiogenic effects and underlying mechanisms of the effects of crocetin and crocin have not been investigated and compared. The anti-angiogenic effects of crocetin and crocin were tested on human umbilical vein endothelial cells (HUVECs) in vitro, and in zebrafish in vivo. In vivo, crocetin (20 μM) and crocin (50 and 100 μM) significantly inhibited subintestinal vein vessels formation, and a conversion process between them existed in zebrafish, resulting in a difference in their effective concentrations. In the HUVEC model, crocetin (10, 20 and 40 μM) and crocin (100, 200 and 400 μM) inhibited cell migration and tube formation, and inhibited the phosphorylation of VEGFR2 and its downstream pathway molecules. In silico analysis further showed that crocetin had a higher ability to bind with VEGFR2 than crocin. These results suggested that crocetin was more effective than crocin in inhibiting angiogenesis through regulation of the VEGF/VEGFR2 signaling pathway. These compounds, especially crocetin, are potential candidate natural biomedicines for the management of diseases associated with abnormal blood vessel growth, such as age-related macular degeneration.